THE MONITOR-"CLIENT" RELATIONSHIP - Root, Veronica (Virginia law review, 2014)
Corporate compliance monitors are everywhere. From Foreign Corrupt Practices Act ("FCPA") violations to securities fraud to general violations of federal law-compliance monitors are a constant in today's society. When a federal or state governmental entity determines that a corporation has engaged in wrongdoing or violated federal law, it often enters into an agreement with the corporation requiring the corporation to retain a corporate compliance monitor. Despite its name, a monitor is often not charged with "monitoring compliance." Instead, a monitor, oftentimes a lawyer but sometimes an accountant or other highly skilled professional, is retained to investigate the compliance failure that resulted in the legal or regulatory violation, assess the cause of the compliance failure, and analyze the company's unique business structures against the legal and regulatory requirements. This allows a monitor to provide an individualized set of recommendations for the corporation to implement.